2009
DOI: 10.1353/sof.0.0184
|View full text |Cite
|
Sign up to set email alerts
|

Drive-bys and Trade-ups: Examining the Directionality of the Crime and Residential Instability Relationship

Abstract: Most prior research testing the hypothesis of the social disorganization theory that residential instability increases crime has used cross-sectional data. Using a unique dataset linking home sales address matched to census tracts with crime data in Los Angeles, we test the direction of this relationship using a six-year panel data design. We also test whether crime acts as a generator of transition and decline in neighborhoods by testing its eff ect on property values the following year. Our fi ndings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 96 publications
(89 reference statements)
2
59
0
1
Order By: Relevance
“…Hipp, Tita and Greenbaum (2009) found that increased property and violent crime rates predicted increased housing turnover (and, in the case of violent crime, lower home values) in the neighbourhood during the subsequent year, but not vice versa, suggesting that crime was more a driver of neighbourhood change than a response to it. However, Hipp (2010) found that neighbourhood concentrated disadvantage did have a positive relationship with crime rates a decade later and vice versa, suggesting that crime does respond to endogenously produced changes in neighbourhood economic composition.…”
Section: The Challenges Of Measuring Causal Relationshipsmentioning
confidence: 96%
“…Hipp, Tita and Greenbaum (2009) found that increased property and violent crime rates predicted increased housing turnover (and, in the case of violent crime, lower home values) in the neighbourhood during the subsequent year, but not vice versa, suggesting that crime was more a driver of neighbourhood change than a response to it. However, Hipp (2010) found that neighbourhood concentrated disadvantage did have a positive relationship with crime rates a decade later and vice versa, suggesting that crime does respond to endogenously produced changes in neighbourhood economic composition.…”
Section: The Challenges Of Measuring Causal Relationshipsmentioning
confidence: 96%
“…First, there are equally plausible reasons that causation runs in the opposite way than is popularly conceived. Absentee landlords in neighborhoods with rising crime rates (perhaps having nothing to do with foreclosures) will likely be faced with falling property values and skyrocketing vacancies as demand for their neighborhoods withers (Hipp, Tita and Greenbaum, 2009;Hipp 2010). They may respond by reducing upkeep, withholding property tax payments and, in extreme cases, defaulting on their mortgages.…”
Section: Foreclosures Crime and Neighborhood Dynamics: Past Researchmentioning
confidence: 99%
“…In response to a growing recognition of the need for a careful consideration of the concept of place and of how place can be operationalized for the systematic study of crime, Hipp (2007) argues for a move toward using geographically smaller units of analysis and, correspondingly, less aggregated data in the spatial analysis of crime (see also Hipp et al 2009). For example, Hipp (2010) describes a unit of analysis for spatial modeling that he calls ''micro-neighborhoods'' which consist of around 10 households.…”
Section: Defining Place For Spatial Analysismentioning
confidence: 99%
“…Places, therefore, are never natural, preformed, or given and there is no such thing as the 'right' scale for any given research topic or interest. Hipp (2007Hipp ( , 2010, Hipp et al (2009), and others are to be commended for suggesting approaches that consciously attempt to deal with the challenges posed by MAUP. But just as with grid-based approaches, the 'smaller is better' micro-scale approach to place in criminology must still wrestle with the problems of place as something that is ultimately socially constructed and therefore contested and subject to change as well as with the perhaps more familiar technical issues of MAUP.…”
Section: Defining Place For Spatial Analysismentioning
confidence: 99%
See 1 more Smart Citation